AKUNTABILITAS TRANSPARANSI DAN PENGAWASAN TERHADAP PENGELOLAAN ALOKASI DANA DESA - Azima, Fauzana; Putri, Annie Mustika; Azhari, Intan Putri (Universitas Muhammadiyah Palembang, 2022)
This study aims to determine the effect of accountability, transparency and supervision on the management of village fund allocations in the Kamang Baru sub-district and to determine the accountability, transparency and supervision of the management of village fund allocations in Nagari Sungai Botuang. The population in this study is the nagari government apparatus in the Kamang Baru sub-district. Consisting of 50 samples from each nagari apparatus totaling 10 respondents. The sampling method in this study was purposive sampling for quantitative and interviews using triangulation techniques. This study uses a mixed method (mix method) a combination of 2 approaches at once (quantitative & qualitative) using an explanatory sequential design. The analytical method used is multiple linear regression analysis using SPSS version 22 (quantitative) and data validity assurance techniques (qualitative). Based on the results of the study, it was concluded that the accountability variable had no effect on the management of village fund allocations and transparency and supervision had an effect on the allocation of village funds.